Fronto-ethmoidal mucoceles: a study of 25 cases - Prajapati, Viral; Khilnani, Ajeet Kumar; Gami, Gambhirsang; Bhalodiya, Neena; Gupta, Devang (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2016)
Background: Paranasal sinus mucoceles are quite rare and a comprehensive study regarding their incidence, presentations, management and complications is significantly lacking in our geographical area which led to our prospective study. Fronto-ethmoidal mucoceles are the most common expansile lesions of the paranasal sinuses. Methods: This is a prospective study of 25 cases of patients presenting with fronto-ethmoidal mucoceles in a tertiary care hospital in Ahmedabad. All patients were managed surgically through endoscopic approach. Results: The study comprised of 25 cases of fronto-ethmoidal mucoceles. The average age of the patients was 47.72 years with a range of 21–75 years. 16 patients (64%) were females. The most common involvement was of frontal sinus (16 cases, 64%). The most common presenting symptom was displacement of eyeball (68% cases). The most common presenting sign was proptosis, present in 68% cases. Endoscopic sinus surgery was the most commonly used modality of treatment of frontal mucocele and fronto-ethmoidal mucoceles (23 cases). In 2 cases combined approach surgery (endoscopic and external) was done. Conclusions: Mucoceles most commonly occur between 4th to 7th decades of life. In most cases no predisposing factor is identified. The diagnosis is based on the history, physical examination and radiological findings. CT is the preferred imaging modality for mucoceles.Endoscopic endonasal surgery is currently the most commonly used surgical approach.